Improving Literacy in Children with the Concept of Environmental Education through the Surrounding Environment - Nia Anggita; Feby Pelani Trisnawati; Moriena Widya; Titin Sunaryati (JOURNAL INCLUSIVE SOCIETY COMMUNITY SERVIES, 2024)
This community service program was carried out in Kecamatan Cikarang Timur Kabupaten Bekasi. Some of the main problems that are a problem in Kecamatan Cikarang Timur Kabupaten Bekasi are the lack of optimal literacy knowledge of the community regarding the potential of the surrounding environment. The results of this PKM activity are described through the role of students as agents of change as a form of local knowledge, which can be used as a means of socializing the importance of awareness to improve literacy skills by getting to know the surrounding environment more closely. The process of introducing literacy to children through the concept of natural tadabur in the surrounding environment is carried out through three approaches, namely: socialization, mentoring, and direct learning about the environment.